2020
DOI: 10.3390/toxins12120803
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin in the Treatment of Headache

Abstract: Botulinum toxin type A has been used in the treatment of chronic migraine for over a decade and has become established as a well-tolerated option for the preventive therapy of chronic migraine. Ongoing research is gradually shedding light on its mechanism of action in migraine prevention. Given that its mechanism of action is quite different from that of the new monoclonal antibodies directed against calcitonin gene-related peptide (CGRP) or its receptor, it is unlikely to be displaced to any major extent by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 60 publications
0
33
0
5
Order By: Relevance
“…An alternative migraine treatment that has gained traction is the targeted blockade of CGRP exocytosis. In fact, botulinum neurotoxin type A (BoNT/A), a potent and specific inhibitor of transmitter release [25,26] due to truncation and inactivation of SNAP-25 (synaptosomal-associated protein with M r = 25k), received FDA approval (BOTOX ® , a complex of BoNT/A and non-toxic proteins) for treating chronic migraine but not the episodic form [27]. This came after BOTOX ® injections were shown in certain patients to reduce the frequency and severity of headache episodes in the Phase III Research Evaluating Migraine Prophylaxis (PREEMPT) series of clinical trials [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative migraine treatment that has gained traction is the targeted blockade of CGRP exocytosis. In fact, botulinum neurotoxin type A (BoNT/A), a potent and specific inhibitor of transmitter release [25,26] due to truncation and inactivation of SNAP-25 (synaptosomal-associated protein with M r = 25k), received FDA approval (BOTOX ® , a complex of BoNT/A and non-toxic proteins) for treating chronic migraine but not the episodic form [27]. This came after BOTOX ® injections were shown in certain patients to reduce the frequency and severity of headache episodes in the Phase III Research Evaluating Migraine Prophylaxis (PREEMPT) series of clinical trials [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies reported benefits from the use of onabotulinumtox-inA to treat migraine. In 2002, several headache experts indicated that onabotulinumtoxinA was safe and effective for prophylactic and acute treatment of migraine [13]. In 2010, the United States FDA approved Botox® for the treatment of chronic migraine.…”
Section: Onabotulinumtoxina and Headachesmentioning
confidence: 99%
“…Upon activation by stimuli, the sensory nerve endings of Cfibers in the meninges release neuropeptides. The role of on-abotulinumtoxinA in blocking the release of these neuropeptides from peripheral C-fiber nerve endings is most likely the key mechanism that underlies its therapeutic action against chronic migraine [13].…”
Section: Onabotulinumtoxina and Chronic Migrainementioning
confidence: 99%
“…Intra-articular injection of BoNT/A complex can reduce joint pain severity with a significant improvement in function [14][15][16]. Moreover, BoNT/A complex (BOTOX) can also alleviate headache pain symptoms for a portion of migraine patients [16][17][18]. Currently, botulinum toxin injections have been US FDA approved for chronic migraines.…”
Section: Introductionmentioning
confidence: 99%